Effects of different sleeping postures on intraocular pressure and ocular perfusion pressure in healthy young subjects - Lee, Tae-Eun; Yoo, Chungkwon; Kim, Yong Yeon (Ophthalmology (Rochester, Minn.), 2013)
To investigate the effects of different sleeping positions of head and body on intraocular pressure (IOP) and ocular perfusion pressure (OPP) in healthy, young subjects. Prospective, comparative case series. Twenty healthy young Korean subjects. We measured IOP and blood pressure (BP) with the subjects seated and recumbent, including supine, right lateral decubitus, left lateral decubitus, prone with right head turn, and prone with left head turn positions. We measured IOP using an Icare tonometer in both eyes 5 minutes after assuming each position in a randomized sequence. We calculated the OPP using the formulas based on the mean BP adjusted for the height of the eye over the heart. The eye on the lower side in the lateral decubitus or prone with head turn position was termed the dependent eye. Difference in IOP and OPP of the dependent and nondependent eyes during changes of sleeping positions of body and head. Mean IOP of right and left eyes while sitting was significantly lower than that measured in each recumbent position (all P<0.001). The OPPs in both eyes were significantly higher in all recumbent positions than in a sitting position (all P<0.001). Mean IOP of the dependent eyes was higher than that of the nondependent eyes in the lateral decubitus positions and in the prone positions with head turns (all P<0.001). No significant intereye difference in OPP was found for any position. Among IOPs measured in the recumbent positions, mean IOP of the dependent eye in the lateral decubitus position or in the prone position with head turn was significantly higher than that of the ipsilateral eye in the supine position (all P<0.0001). All sleeping positions of head and body resulted in an elevation of IOP and an increase in the calculated OPP compared with the sitting position in healthy, young subjects. The postural change from supine to lateral decubitus or prone with head turn position increased the IOP of the dependent eyes without significant alteration in OPP in healthy awake subjects. Further research is needed under nocturnal conditions in a sleep laboratory. The authors have no proprietary or commercial interest in any of the materials discussed in this article.